Pemetaan Peminatan dan Sekolah Lanjutan Pada Siswa Kelas IX MTs Al Maarif 01 Singosari - Romdhiyah, Siti Nuril (Maliki Interdisciplinary Journal, 2025)
This study aims to develop a strategy for mapping interests and planning further education for ninth-grade students at MTs Almaarif 01 Singosari. The process was carried out through psychoeducation on the concept of career planning, distribution of questionnaires to assess interests and academic abilities, and individual and group counseling. Data obtained from 182 students were classified into four groups based on their career readiness and decisions. The results showed that most students experienced confusion in determining their career and secondary school choices, thus requiring appropriate guidance intervention. This method was effective in helping students recognize their potential and overcome obstacles in career decision-making.